Composite cervical adenocarcinoma composed of adenoma malignum and gastric type adenocarcinoma (dedifferentiated adenoma malignum) in a patient with Peutz Jeghers syndrome. Issue 10 (27th September 2010) - McCluggage, W Glenn; Harley, Ian; Houghton, Joseph P; Geyer, Felipe C; MacKay, Alan; Reis-Filho, Jorge S
Abstract : An unusual cervical adenocarcinoma is reported in a 50-year-old woman with a history of Peutz Jeghers syndrome. The carcinoma contained two morphologically distinct and spatially separate components, one comprising typical well differentiated adenoma malignum and the other a moderately differentiated neoplasm, in keeping with gastric type adenocarcinoma. Both components were positive for HIK1083 and MUC6 and negative for p16, and did not contain human papillomavirus. It is believed that such a composite tumour has not been described in the literature. It is believed that the component of gastric type adenocarcinoma arose through a process of dedifferentiation within adenoma malignum and we provide circumstantial molecular evidence in support of the interpretation that both components may be clonally related in that they displayed an extra copy of chromosome 7. This raises the possibility of a relationship between these two uncommon types of cervical adenocarcinoma, both of which are thought to exhibit gastric differentiation.